PEMIKIRAN SAINS-SUFISTIK ORANG BUGIS DALAM NASKAH KUTIKA UGI’ SAKKE RUPA - Rahmatia, Rahmatia; Abdullah Maulani (Jurnal Lektur Keagamaan, 2021)
This article discusses the contents of the manuscript entitled Kutika Ugi' Sakke Rupa (KUSR) or Bunga Rampai Kutika Bugis. KUSR explains the method of calculating the good and bad times of the Bugis people. KUSR has a superior value to similar kutika scripts that only contain one or two methods. KUSR collectsseveral methods of calculating time which mostly accepts literature from the Islamic world in the Middle East and North Africa, suchas the works of Sheikh Aḥmad bin Muḥammad Ramaḍān al-Makki and Abu al-'Abbās Aḥmad bin ‘Alī al-Būnī. In addition, Ibn 'Arabī thought also played an important role in the construction of the KUSR text through the explanation of wahdāt al-wujūd understanding and remem-brance related to the elements of Islamic Sufism. In this regard, this article analyzes the relationship between the influence of Islamic Sufism and the Kutika method of calculation, especially in the 19th century. Therefore, a philological approach related to the study of texts and the history of manuscripts to understand the background of Islamic influence is an important thing to do in this study. This aims to reveal the form of Islamic influence contained in the KUSR text and its relation tothe development of Islam in South Sulawesi. Thus, Islamic discourses, especially Sufism, can be seen as an influential factor in the transmission of science and astro-nomy in the 19th century Bugis society. Keywords: Kutika, Bugis, Natural Science, Sufism.   Artikel ini mendiskusikan isi naskah yang berjudul Kutika Ugi’ Sakke Rupa(KUSR) atau Bunga Rampai Kutika Bugis. KUSR menjelaskan metode perhitungan waktu baik dan buruk masyarakat Bugis. KUSR memiliki nilai ungul daripada naskah kutika serupa yang hanya memuat satu atau dua metode. KUSR menghimpun beberapa metode hitungan waktu yang banyak meresepsi literatur-literatur yang berasal dari dunia Islam di Timur Tengah dan Afrika Utara, seperti karya-karya Syekh Ahmad bin Muhammad Ramadhân al-Makki dan Abu al-‘Abbas Ahmad bin Ali al-Būnī. Selain itu, Ibnu ‘Arabī juga memegang peranan penting dalam konstruksi teks KUSR melalui penjelasan paham wahdāt al-wujūddan zikir-zikir yang berkaitan dengan unsur-unsur sufisme Islam. Sehubungan dengan hal tersebut, artikel ini menganalisis kaitan antara pengaruh sufisme Islam dan metode hitungan Kutika, khususnya pada abad ke-19. Oleh sebab itu, pendekatan Filologi terkait kajian teks dan sejarah naskah untuk memahami latar belakang pengaruh Islam menjadi hal yang penting dilakukan dalam studi ini. Hal ini bertujuan untuk mengungkap bentuk pengaruh Islam yang terdapat dalam naskah KUSR dan kaitannya dengan perkembangan Islam di Sulawesi Selatan. Dengan demikian, wacana-wacana keislaman terutama tasawuf dapat dilihat sebagai faktor yang berpengaruh terhadap transmisi ilmu sains dan falak masyarakat Bugis abad ke-19. Kata kunci: Kutika, Bugis, Sains, Sufisme.